Future Climate Predicts Range Shifts and Increased Global Habitat Suitability for 29 Aedes Mosquito Species - Xueyou Zhang; Hongyan Mei; Peixiao Nie; Xiaokang Hu; Jianmeng Feng (Insects)
Aedes mosquitoes (Diptera, Culicidae) are the major vectors for many mosquito-borne diseases. Here, we retrieved 878,954 global occurrences of 29 Aedes mosquito species and 30 candidate predictors at a global scale. We created a unified frame and built 29 multi-algorithm species distribution models to project the ranges and overlapped them to examine the range-overlap hotspots under future scenarios. We detected expanded ranges in most Aedes mosquito species, and a substantial increase in the index of habitat suitability overlap was detected in more than 70% of the global terrestrial area, particularly in Europe, North America, and Africa. We also identified extensive range overlap, which increased in future scenarios. Climatic factors had a more significant influence on range dynamics than other variables. The expanded ranges of most Aedes mosquito species and the substantial increase in the overlap index of habitat suitability in most regions suggest globally increasing threats of Aedes-borne epidemic transmission. Thus, much stricter strategies must be implemented, particularly in Europe, North America, and Africa. As climate change increases habitat suitability and expands ranges in most Aedes mosquito species, mitigating future climate change will be a key approach to combatting their impacts.